INTERVENSIPEMERINTAH KOTA PONTIANAK DALAM PEMBERDAYAAN SOSIALEKONOMI KELOMPOKTANIALOE VERA DI KOTA PONTIANAK - NUR, FATMAWATY (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2018)
Aloe Vera centre in the Siantan Hulu sub-district is one of the agribusiness areas that will be used as an agrotourism and agricultural icon in West Kalimantan. To keep this center as an icon of agriculture in West Kalimantan, synergy between all elements, especially farmer groups, the private sector and the Pontianak city government, is needed. This research is to examine the extent of the role and intervention of the Pontianak City Government in increasing the socio-economic empowerment of Aloe vera farmers groups to improve their welfare. The data analysis used is qualitative analysis with a descriptive approach. The results of the study show that the role of the Pontianak city government in empowering the socio-economic life of the Aloe Vera farmer group is still not optimally. This is indicated by the intervention process at the evaluation stage does not optimally because there are psychological factors of farmers who are starting to be reluctant to cultivate aloe vera so that Aloe Vera productivity was decreases. The empowerment program and coaching carried out by the Pontianak city government have been going well but still cannot overcome the marketing problem even though terminal agribusiness institutions have been formed whose reality does not function optimally, because farmers do not understand the intent and purpose of developing agribusiness terminals. Socio-economic life of farmer groups, judging from the level of their welfare, still needs attention from the Pontianak city government because most farmers still cannot make the farming of aloe vera as their main source of income.Keywords : Intervention, Pontianak City Government, Aloe Vera Farmers